PENGARUH CAPITAL INTENSITY, INVENTORY INTENSITY, INSTITUTIONAL OWNERSHIP SEBAGAI VARIABEL MODERASI TERHADAP TAX AVOIDANCE - Sri Muliawaty; Tubagus Arya Abdurachman (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aims to determine the influence of capital intensity, inventory intensity, institutional ownership as moderation variables on tax avoidance in energy companies listed on the IDX in 2017-2021. This type of research is associative quantitative, where research methods based on the philosophy of positivism, are used to examine in certain populations or samples, which are in the nature of asking the influence of two or more variables on other variables. The type of data used is secondary data, namely financial statement data obtained from the IDX. The sampling method in this study used purposive sampling techniques with certain criteria. The total amount of data obtained in this study was 45 financial statements from 9 companies. The testing in this study was assisted by the Eviews12 software, and the model used was the regression of the Fixed effect Model (FEM) approach panel data. The results of this study show that simultaneously capital intensity, inventory intensity together affect tax avoidance. Meanwhile, partial capital intensity does not affect tax avoidance, while inventory intensity has a positive effect on tax avoidance, institutional ownership moderation is unable to strengthen the capital intensity relationship to tax avoidance, and institutional ownership moderation is unable to strengthen inventory intensity relationship to tax avoidance